Social Media Marketing Management How to Penetrate Emerging Markets and Expand Your Customer Base. - Hinson, Robert (Robert Ebo); Mhlanga, David; Osei-Frimpong, Kofi.; Doe, Joshua (Oxford : Productivity Press, 2024)
This book seeks to provide practical guidance on the use of social media in the firm's operations. While it provides practical perspectives by addressing contemporary issues in relation to social media marketing practices, this book will also serve as a relevant teaching text in social media marketing.
Chapter 5 Social Networking Sites: A Focus on Mobile Marketing Strategies -- Chapter Outline -- Chapter Outcome -- Introduction -- Growth of Mobile Connectivity and Device Use in Developing Economies -- Mobile Connectivity and Social Media -- Mobile App Platforms -- Social Media -- Anthropology (ANT) Approach to Social Media -- Mobilising Your Brands -- Mobile Brand Engagement -- Designing a Mobile Brand Engagement Campaign -- Designing Mobile Apps for Mobile Shopping -- Mobile Payment Applications -- Characteristics of Mobile Payment Methods -- Types of Mobile Payment Applications
Description based upon print version of record.
Buy Buttons and Location Identification on Social Networking Sites
Keywords: Marketing; Social media; BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Business Communication / General